Safety and feasibility of adjuvant chemotherapy with S-1 in Japanese breast cancer patients after primary systemic chemotherapy: a feasibility study - Shigekawa, Takashi (BMC Cancer, 2015)
BACKGROUND: Advanced breast cancer patients have a higher risk of postoperative recurrence than early-stage breast cancer patients. Recurrence is believed to be caused by the increase in micrometases, which were not eradicated by preoperative or postoperative chemotherapy. Therefore, a new therapeutic strategy that can improve treatment efficacy is mandatory for advanced breast cancer. S-1 was shown to be effective and safe in Japanese metastatic breast cancer patients treated with previous chemotherapy, including anthracyclines. Thus, in this study, we evaluated S-1 as adjuvant chemotherapy in breast cancer patients after standard primary systemic chemotherapy. METHODS: The treatment consisted of 18 courses (a 2-week administration and a 1-week withdrawal; one year) administered at 80–120 mg/body/day. In cases judged to require postoperative radiotherapy, it was concurrently initiated on Day 1 of the study. If the estrogen receptor and/or human epidermal growth factor receptor 2 were positive, endocrine therapy and/or trastuzumab were permitted, concurrently. RESULTS: Of the 45 patients enrolled between September 2007 and September 2009 from 3 institutions, 43 patients were eligible. Thirty-two of the 43 (74.4%) patients received concurrent radiotherapy. Twenty-two of the 43 (51.2%) patients completed the scheduled courses of chemotherapy. The most common reasons for withdrawal of treatment were subjective symptoms, such as nausea, anorexia, or general fatigue during the first 9 courses of treatment in 9/43 (20.9%) patients, recurrence in 7/43 (16.3%) patients, and adverse events in 5/43 (11.6%) patients. The cumulative percentage of administration for 365 days was 66.4% (95% confidence interval: 50.8–79.1%). Although grade 3 neutropenia (9.3%), leukopenia (4.7%), and diarrhea (4.7%) were observed, they were manageable. No grade 4 adverse effects were observed. CONCLUSIONS: The percentage of Japanese breast cancer patients completing the 18-course treatment and the cumulative percentage of administration for 365 days using S-1 after standard primary systemic chemotherapy were similar with the results of another study of adjuvant chemotherapy for the Japanese gastric cancer patients with no severe adverse effects. A phase III trial investigating the usefulness of adjuvant S-1 is now ongoing in Japan, and it is expected that S-1 will have a significant survival benefit in breast cancer patients. UMIN000013469.